Bounded Subsets of Classes MpX of Holomorphic Functions. (8th October 2017) - Iida, Yasuo
Abstract : Some characterizations of boundedness in M p ( X ) will be described, where M p ( X ) ( 0 < p < ∞ ) are F -algebras which consist of holomorphic functions defined by maximal functions.